Effects of stage of gestation and litter size on intrauterine growth in rabbits - Cury, Paulo Roberto; Nunes, José Roberto Veloso (Pesquisa Agropecuaria Brasileira, 1991)
Intrauterine growth of Norfolk rabbits was studied from the 20th day of gestation until the parturition (31st day). A theoretical equation was adjusted for fetuses body weight. The exponential model was tested by stepwise regression technique after linearization. Both stage of gestation (t) and number of fetuses (n) had significant effects on the growth rate. The following equation was proposed to describe the weight of the pups: Ŵ = exp. (-12,9772).n.exp. (0,991264 - 0,014007.t-0,00039.n)t (with R2 = 0,9932). The biological coherence and the interpretation of the coefficients permited us to conclude that similar models could be used for other multiparous species. This model can also be used with or without the presence of different factors related to fetal growth.